From Strategy to Fluency: EFL Learners’ Preferences for Cognitive Learning Strategies to Overcome Psychological and Linguistic Challenges in Speaking - Agustina, Rahmawati; Dio Resta Permana; Dita Rizki Anggraini (Tarling : Journal of Language Education, 2025)
English as an international language has a crucial role, especially focusing on speaking skill among EFL learner. Many Indonesian students face difficulties in speaking English due to linguistic challenges (vocabulary, grammar, pronunciation) and non-linguistic factors (anxiety, low motivation, lack of confidence). The 2024 English Proficiency Index places Indonesia in the "Low" category, highlighting the need for effective cognitive learning strategies to overcome these challenges. This research aims to identify the most frequently used cognitive strategies among English Education students at IGM University and analyze how these strategies relate to their speaking proficiency. Employing a qualitative descriptive approach with purposive sampling of 76 students from various semesters, data were collected via open-ended questionnaires and in-depth semi-structured interviews with nine participants. Analysis using interactive models and thematic approaches found that repetition and practice, problem-solving and transfer, and elaboration and integration are dominant cognitive strategies. The most usage strategy users tended to exhibit higher confidence and better vocabulary handling, while the least strategy users preferred reflective, individual strategies. Both prefer for interactive methods like role-play and group discussions. Recommendations emphasize adaptive, personality-sensitive teaching approaches and encourage learners to explore diverse strategies consistently. This study contributes to developing inclusive and effective English-speaking instruction.